2013
DOI: 10.1007/s11121-013-0368-8
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Ambivalence, Friend Norms, and Adolescent Drug Use

Abstract: This study assessed the moderating effects of attitudinal ambivalence on adolescent marijuana use in the context of the theory of planned behavior (TPB). With data from the National Survey of Parents and Youth (N=1,604), two hierarchical multiple regression models were developed to examine the association of ambivalent attitudes, intentions, and later marijuana use. The first model explored the moderating effect of ambivalence on intentions to use marijuana; the second tested the moderation of ambivalence on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
44
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 64 publications
9
44
0
Order By: Relevance
“…These findings indicate that the incorporation of TPB and life skills into the intervention program helped promote participants' attitudes and subjective norms, and may potentially facilitate reducing illicit drug use. Our findings are in keeping with those from previous TPB studies that have demonstrated associations between attitudes and intentions and consequent illicit drug (marijuana) use [24] and between attitudes and subjective norms and the intention to use illicit drugs [25]. The effectiveness of skills-based drug use prevention programs has been demonstrated by a systematic review.…”
Section: Discussionsupporting
confidence: 90%
“…These findings indicate that the incorporation of TPB and life skills into the intervention program helped promote participants' attitudes and subjective norms, and may potentially facilitate reducing illicit drug use. Our findings are in keeping with those from previous TPB studies that have demonstrated associations between attitudes and intentions and consequent illicit drug (marijuana) use [24] and between attitudes and subjective norms and the intention to use illicit drugs [25]. The effectiveness of skills-based drug use prevention programs has been demonstrated by a systematic review.…”
Section: Discussionsupporting
confidence: 90%
“…The more The attitude of adolescents who support drug use, the bigger their possibility to use drugs in the future. The results of Hohman's (2014) researchreplicate typical findings in the TPB that attitudes should predict behavioral intentions. This influence may reflect teenagers' temporal dependence on drug use attitudes early in adolescence, most have a negative attitude towards drugs, but over time, the valence of attitudes becomes more positive (Johnston et al, 2010).…”
Section: Effect Of Behavioral Control Perceptionon Drug Use Through supporting
confidence: 71%
“…Theoretically, it can affect behavior either directly or indirectly. Intention becomes the attitude intermediary variable, the perception of behavioral control, subjective norms, and behavior (Hohman, 2014). 3.…”
Section: Effect Of Behavioral Control Perceptionon Drug Use Through mentioning
confidence: 99%
“…This finding suggests that the subgoal of the application to destigmatize the population of substance users (those who consume either legal or illegal substances) might miss the aim: instead of facilitating social tolerance it may indirectly promote an accepting attitude toward substance use itself. According to Hohman and colleagues [52] attitudes toward psychoactive substances -especially ambivalent attitudes -can affect substance use behavior. An increase in past month energy drink consumption was associated with higher frequencies of exercise.…”
Section: Discussionmentioning
confidence: 99%